Internet of Things and secure smart environments : successes and pitfalls - Ghosh, Uttam; Rawat, Danda B., 1977-; Datta, Raja; Pathan, Al-Sakib Khan (Boca Raton : CRC Press, Taylor & Francis Group, 2021)
The main goal of Internet of Things (IoT) is to make secure, reliable, and fully automated smart environments. However, there are many technological challenges in deploying IoT. This includes connectivity and networking, timeliness, power and energy consumption dependability, security and privacy, compatibility and longevity, and network/protocol standards. Internet of Things and Secure Smart Environments: Successes and Pitfalls provides a comprehensive overview of recent research and open problems in the area of IoT research. Features: Presents cutting edge topics and research in IoT Includes contributions from leading worldwide researchers Focuses on IoT architectures for smart environments Explores security, privacy, and trust Covers data handling and management (accumulation, abstraction, storage, processing, encryption, fast retrieval, security, and privacy) in IoT for smart environments This bookcovers state-of-the-art problems, presents solutions, and opens research directions for researchers and scholars in both industry and academia.
LIST OF FIGURESLIST OF TABLESPREFACEACKNOWLEDGEMENTSEDITORSCONTRIBUTORSChapter 1 Wireless Localization for Smart Indoor EnvironmentsRavi Sharma and Venkataramana BadarlaChapter 2 An Approach towards GIS Application in Smart City Urban PlanningSourav Banerjee, Chinmay Chakraborty, and Debashis DasChapter 3 A Review of Checkpointing and Rollback Recovery Protocols for Mobile Distributed Computing SystemsHoussem Mansouri and Al-Sakib Khan PathanChapter 4 Softwarized Network Function Virtualization for 5G: Challenges and OpportunitiesDeborsi Basu, Raja Datta, and Uttam GhoshChapter 5 An Effective Deployment of SDN Controller in Smart City RenovationMadhukrishna Priyadarsini and Padmalochan BeraChapter 6 Flying Ad Hoc Networks: Security, Authentication Protocols, and Future DirectionsAiswarya S. Nair and Sabu M. ThampiChapter 7 Investigating Traffic of Smart Speakers and IoT Devices: Security Issues and Privacy ThreatsDavide Caputo, Luca Verderame, Alessio Merlo, and Luca CaviglioneChapter 8 Hardware Security in the Context of Internet of Things: Challenges and OpportunitiesPranesh Santikellur, Rajat Subhra Chakraborty, and Jimson MathewChapter 9 Security Challenges in Hardware Used for Smart EnvironmentsSree Ranjani RajendranChapter 10 Blockchain for Internet of Battlefield Things: A Performance and Feasibility StudyAbel O. Gomez Rivera, Deepak Tosh, and Jaime C. AcostaChapter 11 Internet of Things in 5G Cellular Networks: Radio Resource PerspectiveAjay Pratap and Sajal K. DasChapter 12 An SDN-IoT-Based Framework for Future Smart Cities: Addressing PerspectiveUttam Ghosh, Pushpita Chatterjee, Sachin Shetty, and Raja DattaIndex
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things -- Security measures; COMPUTERS / General; COMPUTERS / Artificial Intelligence; COMPUTERS / Computer Graphics / Game Programming & Design